The complete chloroplast genome of Pleione maculata, an orchid with important ornamental value and medicinal value - He, Lie-Fen (Mitochondrial DNA B Resour, 2021)
Pleione maculata is an epiphytic orchid with significant ornamental value and medicinal value. Here, we report the first complete chloroplast genome of P. maculata. The circular genome was 158,394 bp in length and consisted of a pair of inverted repeats (IR 26,646 bp), which were separated by a large single copy region (LSC 86,603 bp) and a small single copy region (SSC 18,499 bp). It contained 135 genes, including 89 protein-coding genes, 38 tRNAs and 8 rRNAs. Phylogenetic analysis of cp genomes from 41 species of Orchidaceae revealed that all species of Pleione formed one monophyletic clade and P. maculata was located at the base of the genus with high bootstrap values (≥99.1%).